Uterine leiomyoma with RAD51B::NUDT3 fusion: a report of 2 cases - Dundr, Pavel; Machado-Lopez, Alba; Mas, Aymara; Věcková, Zuzana; Mára, Michal; Richtárová, Adéla; Matěj, Radoslav; Stružinská, Ivana; Kendall Bártů, Michaela; Němejcová, Kristýna; Dvořák, Jiří; Hojný, Jan (Virchows Archiv, 2024)
Three main uterine leiomyoma molecular subtypes include tumors with MED12 mutation, molecular aberrations leading to HMGA2 overexpression, and biallelic loss of FH. These aberrations are mutually exclusive and can be found in approximately 80-90% of uterine leiomyoma, in which they seem to be a driver event. Approximately 10% of uterine leiomyoma, however, does not belong to any of these categories. Uterine leiomyoma with HMGA2 overexpression is the most common subtype in cellular and second most common category of usual leiomyoma. In some of these tumors, rearrangement of HMGA2 gene is present. The most common fusion partner of HMGA2 gene is RAD51B. Limited data suggests that RAD51B fusions with other genes may be present in uterine leiomyoma. In our study, we described two cases of uterine leiomyoma with RAD51B::NUDT3 fusion, which occur in one case of usual and one case of highly cellular leiomyoma. In both cases, no other driver molecular aberrations were found. The results of our study showed that RAD51::NUDT3 fusion can occur in both usual and cellular leiomyoma. RAD51B may be a fusion partner of multiple genes other than HMGA2 and HMGA1. In these cases, RAD51B fusion seems to be mutually exclusive with other driver aberrations defining molecular leiomyoma subtypes. RAD51B::NUDT3 fusion should be added to the spectrum of fusions which may occur in uterine leiomyoma, which can be of value especially in cellular leiomyoma in the context of differential diagnosis against endometrial stromal tumors.
Keywords: nádory dělohy; DNA-Binding Proteins; Humans; Cellular leiomyoma; lidé středního věku; DNA vazebné proteiny; Biomarkers, Tumor; fúzní onkogenní proteiny; Female; dospělí; Leiomyoma; leiomyom; lidé; Oncogene Proteins, Fusion; Uterine Neoplasms; nádorové biomarkery; Adult; RAD51B::NUDT3 fusion; ženské pohlaví; Middle Aged; Uterine leiomyoma